Peace Behind Disputes: A Study of Inheritance Settlement through Mediation - Anugerahi Ralina, Warisnu; Mursyid, Mursyid; Salmawati, Salmawati (Faculty of Law, Universitas Muslim Indonesia, 2025)
This research aims to determine and analyze the resolution of inheritance disputes through mediation based on legal provisions. The study reveals inconsistencies in the Supreme Court Regulation Number 1 of 2016 with the Civil Procedure Law in Indonesia, particularly regarding mediation costs and the role of the mediator judge. The mediation process in the Class I A Religious Courts consists of three stages: pre-mediation, mediation, and final implementation. However, the low success rate of mediation is attributed to inhibiting factors, including parties' reluctance to mediate and obstructing the process. This research recommends socialization of the benefits of resolving civil cases through mediation and the Supreme Court's regulation regarding sanctions for parties obstructing the mediation process. Furthermore, parties involved in disputes should prioritize good faith during the mediation process to optimize its success.